TIAM COFFEE SHOP MARKETING STRATEGY USING THE SWOT ANALYSIS METHOD - Islami, Riska Miftahul; Hermawan, Haris; Setianingsih, Wahyu Eko (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
The aim of this research is to find out the SWOT matrix (IFAS and EFAS) at Kedai Kopi Tiam and find out alternative marketing strategies. This research uses the SWOT analysis method, namely strategic planning which is used to evaluate strengths, weaknesses, opportunities and threats. The SWOT model used in this research is a strategy for formulating an analytical framework which is divided into 3 stages, namely the input stage, matching stage and decision stage. Based on the results of the data analysis obtained, it was concluded that Kedai Kopi Tiam occupies quadrant I, which means the company is growing and developing. In this strategy, of course Kedai Kopi Tiam must maintain its strengths and take advantage of existing opportunities to avoid external threats and weaknesses within the company.